1974
DOI: 10.1042/cs0470609
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatic Encephalopathy in the Rat: The Effect of Cross-Circulation

Abstract: 1. The effect of cross-circulation on hepatic encephalopathy (evaluated by electroencephalography; EEG) induced by hepatectomy in the rat was examined.2. Systemiosystemic cross-circulation induced improvement of the altered EEG in only two out of seven liverless rats when the exchange-flow rate was 6.4 ml min-' kg body wt.-', and in all seven liverless rats when the exchange-flow rate was 14.0 ml min-kg body wt.-; the difference is statistically significant (P = 0.01 1). Systemioportal cross-circulation (syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Under this light, portal-systemic shunting plays a critical role, as the main impact of this circulatory disturbance is on the concentration of gut-derived substances that are highly cleared by the liver. Studies of cross-perfusion in animals with experimental HE and liver support systems in humans have shown that clearance of toxic substances present in the blood is more important to improve mental function than the synthetic capacity of the support system [ 5 ]. In patients with liver disease, these toxic substances reach the systemic circulation as a result of portal-systemic shunting or reduced hepatic clearance and produce deleterious effects on brain function.…”
Section: Pathogenesismentioning
confidence: 99%
“…Under this light, portal-systemic shunting plays a critical role, as the main impact of this circulatory disturbance is on the concentration of gut-derived substances that are highly cleared by the liver. Studies of cross-perfusion in animals with experimental HE and liver support systems in humans have shown that clearance of toxic substances present in the blood is more important to improve mental function than the synthetic capacity of the support system [ 5 ]. In patients with liver disease, these toxic substances reach the systemic circulation as a result of portal-systemic shunting or reduced hepatic clearance and produce deleterious effects on brain function.…”
Section: Pathogenesismentioning
confidence: 99%
“…However, experimental and clinical evidence does not support this concept. Cross-perfusion experiments in a rat model of hepatic liver failure showed that depuration of its blood through a normal liver is far more critical for an adequate mental state than the provision of liver-derived blood from a normal animal [21]. For many years, the controversy has centred around the nature of gut-derived toxins.…”
Section: Ammonia and Other Circulating Neurotoxinsmentioning
confidence: 99%
“…Furthermore, in lieu of animal experimentation some laboratories have opted to measure functional hepatocyte activities in hollow fiber devices perfused in vitro, which play IZO role in HE, i.e., the production of albumin. In this context, it should be emphasized that although the pathogenesis of HE is unknown, carefully designed crosscirculation experiments do not support the possibility of a diminished hepatic synthesis of a substance necessary for brain function in FHF (14). Rather, there is a general agreement that a diminished hepatic catabolism of certain (gut-derived) metabolites or endotoxins is taking place (8).…”
mentioning
confidence: 99%